Accumulation of N-acyl-ethanolamine phospholipids in rat brains during post-decapitative ischemia: a 31P NMR study - Birthe Moesgaard; Jerzy W. Jaroszewski; Harald S. Hansen (Journal of Lipid Research, 1999)
Phosphorus-31 nuclear magnetic resonance (31P NMR) spectroscopy has been used to study accumulation of N-acyl-ethanolamine phospholipids in rat brains during post-decapitative ischemia. Lipids were extracted from rat brain homogenates and the extracts were thoroughly washed with aq. potassium ethylenediaminetetraacetic acid (EDTA). The lower organic phases were isolated and evaporated to dryness under a stream of nitrogen and the lipids were redissolved in CDCl3–CH3OH–H2O 100.0:29.9:5.2 (v/v/v) for NMR analysis. Increasing the period of post-decapitative ischemia resulted in an accumulation of two signals in the NMR spectra at 0.18 and 0.22 ppm (relative to the chemical shift of 1,2-diacyl-sn-glycero-3-phosphocholine (PCDIACYL) at –0.84 ppm). These signals were identified as originating from 1,2-diacyl-sn-glycero-3-phospho-(N-acyl)-ethanolamine (NAPEDIACYL) and 1-(1′-alkenyl)-2-acyl-sn-glycero-3-phospho-(N-acyl)-ethanolamine (NAPEPLAS), respectively, by spiking with authentic materials. Additionally, the identification was verified by thin-layer chromatography, which also showed the accumulation of N-acyl-ethanolamine phospholipids. The use of K-EDTA instead of the commonly used Cs-EDTA in the preparation of the NMR samples allowed the separation of the chemical shifts of N-acyl-ethanolamine phospholipids from those of the ethanolamine phospholipids. Moreover, the chemical shift of cardiolipin was moved from 0.15 ppm observed with Cs-EDTA to about 0.31 ppm with K-EDTA. The present study demonstrates that it is possible to detect and quantify post-decapitative accumulation of NAPE subclasses (NAPEDIACYL and NAPEPLAS) in rat brains by the use of 31P NMR spectroscopy. —Moesgaard, B., J. W. Jaroszewski, and H. S. Hansen. Accumulation of N-acyl-ethanolamine phospholipids in rat brains during post-decapitative ischemia: a 31P NMR study. J. Lipid Res. 1999. 40: 515–521.